1973
DOI: 10.1111/j.1365-2672.1973.tb04149.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Metal Cations and pH on the Antibacterial Activity and Uptake of Long Chain Fatty Acids

Abstract: The bactericidal activity of long chain saturated fatty acids was antagonized by alkaline earth metals. The activity of linoleic acid waa less effectively antagonized but was more sensitive to reversal by ferric and stannous ions. With increasing pH value the bactericidal activity of lauric acid decreased but that of the longer chain saturated acids increased. Both Gram positive and Gram negative bacteria reversibly adsorbed fatty acids, Uptake increased with decreasing pH value and increasing chain length. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0
1

Year Published

1979
1979
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(40 citation statements)
references
References 16 publications
0
39
0
1
Order By: Relevance
“…The latter suggests that significant soap formation with C 12:0 had taken place. The reversal of the antibacterial activity of MCFA by Ca supplementation is well documented for C 12:0 (Galbraith et al 1971) and C 14:0 (Galbraith and Miller 1973). Furthermore, Koster (1987) demonstrated that the inhibition of the methanogenic population in biogas reactors due to C 12:0 could be reversed by the addition of an equimolar amount of Ca ions, but only when added together with the fatty acids.…”
Section: Effects Of Calcium On Rumen Microbes and Ruminal Methanogenesismentioning
confidence: 94%
“…The latter suggests that significant soap formation with C 12:0 had taken place. The reversal of the antibacterial activity of MCFA by Ca supplementation is well documented for C 12:0 (Galbraith et al 1971) and C 14:0 (Galbraith and Miller 1973). Furthermore, Koster (1987) demonstrated that the inhibition of the methanogenic population in biogas reactors due to C 12:0 could be reversed by the addition of an equimolar amount of Ca ions, but only when added together with the fatty acids.…”
Section: Effects Of Calcium On Rumen Microbes and Ruminal Methanogenesismentioning
confidence: 94%
“…The presence of calcium ions and, to a lesser extent, magnesium ions is known to reduce the antimicrobial action of LCFA (Galbraith & Miller, 1973). Inclusion of calcium hydroxide in ruminant diets makes it possible to increase rates of fat inclusion substantially without adverse effects on fibre digestibility (Palmquist, 1988;Ohajuruka et al 1991).…”
Section: Antimicrobial Activity Of Dietary Lipidsmentioning
confidence: 99%
“…Short-chain fatty acids are more active at low than at higher pH 10 . Galbraith et al reported that the bactericidal activity of lauric acid decreased with increasing pH value but that of myristic acid and palmitic acid increased 11 . However, the effect of pH on the bactericidal activity of the surfactant calcium salt is largely unknown.…”
Section: Introductionmentioning
confidence: 99%